2018
DOI: 10.5194/angeo-36-1099-2018
|View full text |Cite
|
Sign up to set email alerts
|

On the short-term variability of turbulence and temperature in the winter mesosphere

Abstract: Abstract. Four mesosphere-lower thermosphere temperature and turbulence profiles were obtained in situ within ∼ 30 min and over an area of about 100 by 100 km during a sounding rocket experiment conducted on 26 January 2015 at Poker Flat Research Range in Alaska. In this paper we examine the spatial and temporal variability of mesospheric turbulence in relationship to the static stability of the background atmosphere. Using active payload attitude control, neutral density fluctuations, a tracer for turbulence,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Such simple spectral models which can provide suitable estimates for the 1D velocity spectrum E(k) or scalar spectrum E ϑ (k) as a function of energy dissipation rate at a range of wavenumbers evolved from a series of works (e.g., Driscoll & Kennedy, 1981, 1983Heisenberg, 1948;Lübken, 1992;Lübken et al, 1993;Tatarskii, 1971, and references therein). These models for example, of Driscoll and Kennedy (1985), Heisenberg (1948), andTatarskii (1971) are based on an assumed form for the spectral energy transfer rate (see e.g., Hinze, 1975, for details) and showed a good agreement with universal equilibrium range spectral data measured in the Earth atmosphere (e.g., Lehmacher et al, 2018;Lehmacher & Lübken, 1995;Lübken, 1992Lübken, , 1997Lübken et al, 1993Lübken et al, , 2002Rapp et al, 2004;Strelnikov et al, 2003Strelnikov et al, , 2013.…”
Section: Spectral Model Techniquementioning
confidence: 95%
See 2 more Smart Citations
“…Such simple spectral models which can provide suitable estimates for the 1D velocity spectrum E(k) or scalar spectrum E ϑ (k) as a function of energy dissipation rate at a range of wavenumbers evolved from a series of works (e.g., Driscoll & Kennedy, 1981, 1983Heisenberg, 1948;Lübken, 1992;Lübken et al, 1993;Tatarskii, 1971, and references therein). These models for example, of Driscoll and Kennedy (1985), Heisenberg (1948), andTatarskii (1971) are based on an assumed form for the spectral energy transfer rate (see e.g., Hinze, 1975, for details) and showed a good agreement with universal equilibrium range spectral data measured in the Earth atmosphere (e.g., Lehmacher et al, 2018;Lehmacher & Lübken, 1995;Lübken, 1992Lübken, , 1997Lübken et al, 1993Lübken et al, , 2002Rapp et al, 2004;Strelnikov et al, 2003Strelnikov et al, , 2013.…”
Section: Spectral Model Techniquementioning
confidence: 95%
“…Based on a limited set of data Lübken (1997) and Lübken et al (1993) showed that application of these models reveals values of the derived energy dissipation rates which are close to each other. Since then mostly the model of Heisenberg (1948) has been applied by scientific community for derivation of turbulence energy dissipation rate, ɛ, based on the Lübken's spectral model technique (e.g., Blix et al, 2003;Chandra et al, 2012;Croskey et al, 2004;Das et al, 2009;Kelley et al, 2003;Lehmacher et al, 2006Lehmacher et al, , 2018Triplett et al, 2018). The main reason for that was the relative simplicity of implementation and numerical stability of the Heisenberg (1948) model.…”
Section: Spectral Model Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on turbopause, where ε has a value of zero, Hall et al [5,6] found an annual cycle in its position and studied its long-term pattern of variation. Lehmacher et al [7] examined the relationship between the spatiotemporal variation of the middle atmospheric turbulence and the static stability of the background atmosphere.…”
Section: Introductionmentioning
confidence: 99%